Non Litigation Dispute Resolution in Settlement of Civil Disputes - I Made Wahyu Chandra Satriana; Ni Made Liana Dewi (IHSA Institute, 2021)
Dispute resolution through the courts is considered the main way of solving problems. The judiciary, which is basically formed to adjudicate and resolve problems, but in reality sometimes it is unable to solve the problems faced by the parties, sometimes it even creates new problems. This research discusses how Non-Litigation settlement legal efforts in Civil dispute resolution and Non-Litigation dispute resolution obstacles according to Civil Law. The research method used is an empirical research method by examining and getting answers to problems regarding the settlement and obstacles to non-litigation dispute resolution according to civil law. The result of this research is the settlement of civil disputes, namely by means of non-litigation, which has several forms, namely Negotiation, Mediation and Arbitration. Meanwhile, the obstacle to non-litigation settlement in civil law cases of sale and purchase is about mediation and the validity of the results of the parties' reconciliation.